2010
DOI: 10.1155/2010/362524
|View full text |Cite
|
Sign up to set email alerts
|

Acute, Multiple-Dose Dermal and Genetic Toxicity of Nu-3: A Novel Antimicrobial Agent

Abstract: Nu-3 [butyl-phosphate-5′-thymidine-3′-phosphate-butyl] is a modified nucleotide that has been shown to have antimicrobial activity against a range of bacteria including Pseudomonas aeruginosa. However, data on the toxicological profile of Nu-3 are still lacking. In the present study, the toxicity of Nu-3 was evaluated by the following studies: acute oral toxicity, dermal and mucous membrane irritation, multiple-dose toxicity and genotoxicity in vivo and vitro. The acute oral toxicity test in mice showed that N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Previous studies demonstrated that Nu-3 was efficacious in the treatment of burn-wound infections by Pseudomonas aeruginosa in mice [ 6 ]. Subsequent studies revealed that there was no chronic toxicity to healthy mouse skin when Nu-3 was applied topically [ 7 ], indicating that Nu-3 has a favorable toxicological profile for use as a topical antibiotic. In order to further explore how wide the spectrum of Nu-3 antibacterial activity is, MIC and time-kill experiments were performed with a wide range of Gram-positive and Gram-negative bacteria, including some hospital isolates of meticillin-resistent Staphylococcus aureus (MRSA) and meticillin-susceptible Staphylococcus aureus (MSSA).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that Nu-3 was efficacious in the treatment of burn-wound infections by Pseudomonas aeruginosa in mice [ 6 ]. Subsequent studies revealed that there was no chronic toxicity to healthy mouse skin when Nu-3 was applied topically [ 7 ], indicating that Nu-3 has a favorable toxicological profile for use as a topical antibiotic. In order to further explore how wide the spectrum of Nu-3 antibacterial activity is, MIC and time-kill experiments were performed with a wide range of Gram-positive and Gram-negative bacteria, including some hospital isolates of meticillin-resistent Staphylococcus aureus (MRSA) and meticillin-susceptible Staphylococcus aureus (MSSA).…”
Section: Introductionmentioning
confidence: 99%
“…of FNC (Zhang et al, 2017). FNAs behaves unorthodoxly in case of liver toxicity, where in some studies NAs show significant toxicity to the liver at very low concentration (Sun et al, 2010), and in other no toxicity even at very high concentration (Chen et al, 2013;Inkoom et al, 2020). Organs like the spleen, heart, brain, and lungs are other sites affected by the drug, due to drug accumulation (Jiang et al, 2019;Shi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%